Dermoid Cyst of the Prepontine Cistern and Meckel's Cave: Illustrative Case and Systematic Review - Chung, Lawrance K.; Lagman, Carlito; Duong, Courtney; Nagasawa, Daniel T.; Tucker, Alexander M.; Yong, William H.; Yang, Isaac (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective Dermoid cysts are benign, congenital malformations that account for ∼0.5% of intracranial neoplasms. The authors describe a 42-year-old female with a prepontine dermoid cyst who underwent apparent gross total resection (GTR) but experienced cyst recurrence. To date, very few cases of prepontine dermoid cysts have been reported. The prevalent region where these cysts are located can be difficult to determine. In addition, the authors systematically review the literature to characterize the clinical presentation, anatomical distribution, and surgical outcomes of intracranial dermoid cysts.Design Systematic review.Setting/Participants PubMed, Web of Science, and Scopus databases.Main Outcome Measures Extent of resection, symptom improvement, and recurrence rates.Results A total of 69 patients with intracranial dermoid cysts were identified. Three (4.3%) intracranial dermoid cysts were located in the prepontine cistern. The average age of patients was 33.3 years. The most common presenting symptoms were headache (52.2%) and visual disturbances (33.3%). Intracranial dermoid cysts were distributed similarly throughout the anterior, middle, and posterior cranial fossae (29.0%, 36.2%, and 29.0%, respectively). GTR was achieved in 42.0% of cases. Thirty-four (49.3%) patients experienced symptom resolution. Recurrence rate was 5.8% at a mean follow-up of 2.1 years.Conclusions Intracranial dermoid cysts most often present as headaches and visual disturbances. Intracranial dermoid cysts were found in the anterior, middle, and posterior cranial fossae at similar frequencies but with clear predilections for the Sylvian fissure, sellar region, and cerebellar vermis. Outcomes following surgical excision of intracranial dermoid cysts are generally favorable despite moderate rates of GTR.
Keywords: dermoid cysts; intracranial; prepontine cistern; systematic review